Study of Ambrosia Beetle Population (Coleoptera: Scolytidae) in Indonesian Teak Forests - Alberto Dorval; Makaka Caston (Frontier Advances in Applied Science and Engineering, 2025)
Purwoharjo District is one of the areas in Banyuwangi Regency that has teak forests covering an area of ​​7,677.80 Ha (protected forest) and 37,716.37 Ha (production forest). The climate conditions in the teak forest area of ​​Purwoharjo District provide opportunities for various types of insects (pests) to live and breed in teak forests, especially Ambrosia beetles, both on teak land cultivated in monoculture and polyculture. It is suspected that there is a fairly massive distribution of Ambrosia Beetles in the teak land of Purwoharjo District because these beetles attack a lot of fresh wood that has just been cut down and wood plants such as teak and sengon. Diversity was analyzed using the Shannon-Wiener diversity index (H’), Simpson’s dominance index (D) and Pielou’s evenness index (E), while the similarity index was analyzed using a Venn diagram. Hypothesis testing was carried out using the Independent T-Test using SPSS 20 software. The results of the study showed that there were 7 and 4 species of ambrosia beetles trapped in monoculture and polyculture teak lands. The teak planting pattern did not significantly affect the abundance of ambrosia beetle individuals with an Independent T-test Sig. (2-tailed) value of 0.736; while the planting pattern significantly affected the abundance of ambrosia beetle species with an Independent T-test Sig. (2-tailed) value of 0.000. Coating with sulfur slurry carried out in this study was proven to reduce the distribution of ambrosia beetles by 33 individuals in monoculture teak and 81 individuals in polyculture teak.